2022
DOI: 10.1002/nau.25077
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of penile inversion vaginoplasty and robotic‐assisted peritoneal flap vaginoplasty in obese and nonobese patients

Abstract: Aim: To explore the impact of body mass index (BMI) on the outcomes of gender-affirming vaginoplasty. Methods: A cohort consisting of all gender-affirming vaginoplasties in our practice between September 27th, 2018, and September 1st, 2022 were identified, and data were retrospectively collected. Patients were classified as obese if their BMI was ≥30 kg/m 2 at the time of surgery and nonobese if their BMI was <30 kg/m 2 . Complications were assigned a Clavien-Dindo grade and grouped as Grade ≥2 versus Grade ≤1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Specifically, this categorization may have facilitated the capture of clinically relevant markers of obesity that are less sensitive to daily fluctuations. [30][31][32] Furthermore, our extended postoperative period provided adequate time for potential development of vaginal stenosis and need for revision, which frequently occur outside of the 3-month postoperative period. 33 Maintaining patency of the vaginal introitus is essential in optimizing postoperative sexual well-being and has been associated with improved satisfaction related to body image, relationship stability, and overall quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, this categorization may have facilitated the capture of clinically relevant markers of obesity that are less sensitive to daily fluctuations. [30][31][32] Furthermore, our extended postoperative period provided adequate time for potential development of vaginal stenosis and need for revision, which frequently occur outside of the 3-month postoperative period. 33 Maintaining patency of the vaginal introitus is essential in optimizing postoperative sexual well-being and has been associated with improved satisfaction related to body image, relationship stability, and overall quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ives et al 14 found that BMI was not predictive of postoperative complications, albeit within a much shorter time frame (3 months of follow-up) and without the categorization of patients by WHO obesity class. Specifically, this categorization may have facilitated the capture of clinically relevant markers of obesity that are less sensitive to daily fluctuations 30–32 . Furthermore, our extended postoperative period provided adequate time for potential development of vaginal stenosis and need for revision, which frequently occur outside of the 3-month postoperative period 33 …”
Section: Discussionmentioning
confidence: 99%
“…Among gender affirming surgeries, the use of the robotic surgical system has been most extensively applied to gender affirming vaginal reconstruction. 4,9,[11][12][13][14][15] Non-robotassisted penile inversion vaginoplasty techniques involve dissecting a neovaginal canal between the prostate and the rectum from an external perineal incision and lining that canal with a combination of penile skin flaps, scrotal or abdominal skin grafts, and/or acellular dermal matrix. 16 This technique presents several challenges, including (1) limited visibility of the deepest part of the canal dissection and (2) limited genital tissue for canal lining in cases of penoscrotal hypoplasia.…”
Section: Penile Inversion Vaginoplastymentioning
confidence: 99%